2011
DOI: 10.1103/physrevb.83.155436
|View full text |Cite
|
Sign up to set email alerts
|

Third edge for a graphene nanoribbon: A tight-binding model calculation

Abstract: The electronic and transport properties of an extended linear defect embedded in a zigzag nanoribbon of realistic width are studied, within a tight binding model approach. Our results suggest that such defect profoundly modify the properties of the nanoribbon, introducing new conductance quantization values and modifying the conductance quantization thresholds. The linear defect along the nanoribbon behaves as an effective third edge of the system, which shows a metallic behavior, giving rise to new conduction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 41 publications
1
60
0
7
Order By: Relevance
“…The first one, (2,0), consists of domains with the aligned crystallographic orientations θ L = θ R = θ = 0 • (d ≈ 0.5 nm) and separated by a zigzag-oriented interface of one octagon and two side-sharing pentagons. [16][17][18][19]23 The repeat vector (2,1) of the second one implies θ L = θ R = θ = 10.9 • (d ≈ 0.65 nm) and its interface region includes pentagon-heptagon pairs. 6,17 We would like to note that while we study two representative GBs, (2,0) and (2,1) (corresponding to aligned and misaligned crystallographic orientations), we believe that our findings are generic and remain valid for other GBs in graphene.…”
Section: Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one, (2,0), consists of domains with the aligned crystallographic orientations θ L = θ R = θ = 0 • (d ≈ 0.5 nm) and separated by a zigzag-oriented interface of one octagon and two side-sharing pentagons. [16][17][18][19]23 The repeat vector (2,1) of the second one implies θ L = θ R = θ = 10.9 • (d ≈ 0.65 nm) and its interface region includes pentagon-heptagon pairs. 6,17 We would like to note that while we study two representative GBs, (2,0) and (2,1) (corresponding to aligned and misaligned crystallographic orientations), we believe that our findings are generic and remain valid for other GBs in graphene.…”
Section: Basicsmentioning
confidence: 99%
“…[12][13][14][15] This provides a strong motivation for investigation of morphological, electronic, and spin properties of GBs. A number of studies have been recently reported addressing the band structure, [16][17][18][19][20] spin polarization, 16,17,21,22 electron transport and scattering 12,13,20 in GBs. However, all these studies were limited to the case of electrically neutral graphene, and very little is presently known on how the electronic and transport properties of GBs are modified at nonzero electron densities (i.e., away from the Dirac point).…”
Section: Introductionmentioning
confidence: 99%
“…The first one is an LD-ZGNR whose electronic and transport properties have been previously calculated by a TB model. 19 It has been reported that the line defect behaves as an effective third edge and can be used as a quantum wire. 19 The second one is an LD-BG, in which the line defect has been reported to give rise to the valley filtering effect.…”
Section: Electronic Eigen States Of Dirac Equationmentioning
confidence: 99%
“…19 It has been reported that the line defect behaves as an effective third edge and can be used as a quantum wire. 19 The second one is an LD-BG, in which the line defect has been reported to give rise to the valley filtering effect. 17 To comparing the dispersion relation and the wavefunction obtained by solving the Dirac equation with the TB numerical result, we find both results agree with each other very well in low-energy region.…”
Section: Electronic Eigen States Of Dirac Equationmentioning
confidence: 99%
See 1 more Smart Citation